High Sensitivity Very Low Frequency Receiver for Earthquake Data Acquisition - Achmad Munir; Kusmadi Kusmadi; Kusnandar Kusnandar; Asep Najmurrokhman; Chairunnisa Chairunnisa; Sunubroto Sunubroto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A high sensitivity very low frequency (VLF) receiver is developed based on AD744 monolithic operational amplifier (Op-Amp) for earthquake data acquisition. In research related natural phenomena such as atmospheric noise, lightning and earthquake, a VLF receiver particularly with high sensitivity is utterly required due to the low power of VLF wave signals received by the antenna. The developed receiver is intended to have high sensitivity reception for the signals in frequency range of 10-30 kHz allocated for earthquake observation. The VLF receiver which is portably designed is also equipped with an output port connectable to the soundcard of personal computer for further data acquisition. After obtaining the optimum design, the hardware realization is implemented on a printed circuit board (PCB) for experimental characterization. It shows that the sensitivity of realized VLF receiver is almost linear in the predefined frequency range for the input signals lower than -12dBm and to be quadratic for the higher level input signals.